A cline in seed dormancy helps conserve the environment experienced during reproduction across the range of Arabidopsis thaliana. Issue 1 (7th January 2016) - Burghardt, Liana T.; Metcalf, C. Jessica E.; Donohue, Kathleen
Abstract : PREMISE OF THE STUDY: Understanding the factors shaping range limits is critical given current changes in climate as well as human‐mediated introduction of species into novel environments. Phenological responses to climate influence range limits by allowing plants to avoid conditions that decrease population growth rates. Studying these processes is a challenge due to the joint contributions of both genetic and environmental variation to phenology. METHODS: Using a previously developed model that predicts phenology of three dormancy "genotypes" in four locations spanning the European range of Arabidopsis thaliana, we examined how variation in seed dormancy influences the environmental conditions experienced by reproductive individuals and how those conditions influence reproductive potential. We calculated two metrics: temperature experienced during reproduction and the length of thermal window available for reproduction. KEY RESULTS: Seed dormancy levels determine whether a spring‐flowering life cycle is expressed and thus determine the reproductive environment. A genetic cline in seed dormancy across the range reduces differences in reproductive environment and increases the thermal opportunity for reproduction before conditions become unfavorable for survival. Counter‐intuitively, these putatively local genotypes are predicted to reproduce in slightly cooler conditions in the south than in the north, suggesting that maternal environmental effects on average could induce deeper dormancy in southern seeds reinforcing the observed genetic cline. However, within a location, we found large individual level differences. CONCLUSIONS: Phenological adjustments of early life stages can contribute to the maintenance of consistent reproductive environments experienced by individual plants across ranges despite variable environmental conditions over time and space.